If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 14) = 69 Reorder the terms: 3(14 + x) = 69 (14 * 3 + x * 3) = 69 (42 + 3x) = 69 Solving 42 + 3x = 69 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 3x = 69 + -42 Combine like terms: 42 + -42 = 0 0 + 3x = 69 + -42 3x = 69 + -42 Combine like terms: 69 + -42 = 27 3x = 27 Divide each side by '3'. x = 9 Simplifying x = 9
| z^2+6z-27=0 | | -36=4v+4(v+7) | | 5/6*2/3=x | | -19/35+4/15 | | 3x^2+5=65 | | 9=3x-7 | | -120x+3000=-160x+4000 | | 7+2x=5x-5 | | 4x+2=32 | | 67-3x=9x+16 | | 7/9y+2+5/9y+6 | | 3a+2a=135 | | x-.3x=105 | | 4+8r-3=7r+29-3r | | 6z+18-9=27 | | 5y-5y=-5 | | 22+k=29 | | 4x+3x=9 | | -3z+6z=9z+9-4z | | ln(x)=ln(2)+ln(x-8) | | 5x+28=14x-36 | | 12x-3=3(2x+5) | | -1+3x=10 | | 1ov=60 | | y+y=5 | | 14q+14q+3p-1q= | | 9x-1/4y=5 | | 1/2w +2 = 4 | | 52-9=16 | | 3x^2+18x+81=25 | | ((a+4)/3a)-((2-4a)/6a) | | (a+4)/3a-(2-4a)/6a |